Genetics of Benign Familial Infantile Epilepsies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at Instituto G Gaslini, Genova, Italy and multiple other centers in Italy studied the genetics of benign familial epilepsies of the first year of life and assessed the extent of the genetic overlap between neonatal and infantile seizure syndromes.